PEMBUATAN DAN PENGUJIAN MESIN PERAJANG TALAS - Wardianto, Dedi; Hafni, Hafni; Hadi Perkasa, Mego (Jurnal Teknologi dan Vokasi, 2023)
This taro chopper machine will work when the electric motor is turned on it will rotate then the rotary motion of the machine is transmitted to the pulley by using a v-belt to move the shaft, the disk where the knife will rotate and the taro is ready to be chopped. After the taro is chopped it will come out through the funnel. So far, industry or industrial machinery products have shown very rapid capabilities, both in terms of volume and in terms of the variety of products produced. Product development is not only marked by the fulfillment of public interest in industrial products, both small and large scale but also leads to exports which will increase foreign exchange for the Indonesian state. There are many agricultural communities, one of which is taro because the season is suitable for the territory of Indonesia. With the development of appropriate technological advances, technological tools can be found that can process agricultural products, so thoughts are made on how to increase and ease work or process crops or process taro products to increase selling prices even better. The general aim of the research is to facilitate the slicing of taro for chip entrepreneurs, especially taro chips, and it can also be operated for cutting or slicing such as tempeh, potatoes, sweet potatoes, carrots, etc. The specific purpose for making this tool is to know the capacity of the taro chopper, to know the components that exist in the taro chopper, and to analyze the results of the taro chopper. From the manufacture of the tool, it can be concluded that this taro chopper is operated semi-automatically using an electric motor. This machine chopping method is a single chopper with 1 type of knife that cuts the taro continuously. This taro chopper machine design requires power from an electric motor of HP. The effective capacity of the tool obtained by the taro chopper machine is 33.3 gr/s.